2023
DOI: 10.1111/jre.13183
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis in saliva from periodontally healthy, gingivitis and periodontitis patients

Meaad M. Alamri,
Benjamin Williams,
Adrien Le Guennec
et al.

Abstract: ObjectiveThe aim of this study was to investigate metabolomics markers in the saliva of patients with periodontal health, gingivitis and periodontitis.BackgroundThe use of metabolomics for diagnosing and monitoring periodontitis is promising. Although several metabolites have been reported to be altered by inflammation, few studies have examined metabolomics in saliva collected from patients with different periodontal phenotypes.MethodsSaliva samples collected from a total of 63 patients were analysed by nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…At present, mass spectrometry and nuclear magnetic resonance are the main techniques in metabolomics and have been employed in the exploration of differential metabolites found in the oral microbiome between health and disease. In periodontal diseases, clinical studies revealed alterations in some metabolites between periodontally healthy and diseased individuals [ 157–160 ]. Wei et al .…”
Section: Metabolomics For Probiotic and Prebiotic Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, mass spectrometry and nuclear magnetic resonance are the main techniques in metabolomics and have been employed in the exploration of differential metabolites found in the oral microbiome between health and disease. In periodontal diseases, clinical studies revealed alterations in some metabolites between periodontally healthy and diseased individuals [ 157–160 ]. Wei et al .…”
Section: Metabolomics For Probiotic and Prebiotic Discoverymentioning
confidence: 99%
“…Periodontitis-metabolic biomarkers in saliva, GCF or dental plaque have been investigated for years, but there is no consensus in specific metabolites identified as the disease signature across the studies [ 157 , 159 , 181–183 ]. Nonetheless, targets might include short chain fatty acids, as butyrate has been demonstrated to impact epithelial cell junctions, amongst other influences [ 184 ], protease inhibition to tackle the detrimental proteolytic activity [ 185 ] and oxidative stress pathways to counteract the damage caused [ 186 ].…”
Section: Metabolomics For Probiotic and Prebiotic Discoverymentioning
confidence: 99%